Luteolin-7-O-Glucuronide Improves Depression-like and Stress Coping Behaviors in Sleep Deprivation Stress Model by Activation of the BDNF Signaling - Ryu, Dajung; Jee, Hye Jin; Kim, Sang Yoon; Hwang, Seung Hwan; Pil, Gam Bang; Jung, Yi Sook (Nutrients, 2022)
Stress exposure is a major risk factor for mental disorders such as depression. Because of the limitations of classical antidepressants such as side effects, low efficacy, and difficulty in long-term use, new natural medicines and bioactive molecules from plants with greater safety and efficacy have recently attracted attention. Luteolin-7-O-glucuronide (L7Gn), a bioactive molecule present in Perilla frutescens, is known to alleviate severe inflammatory responses and oxidative stress in macrophages. However, its antistress and antidepressant effects have not been elucidated. The present study aims to explore the antidepressant the effect of L7Gn on stress-induced behaviors and the underlying mechanism in a mouse sleep deprivation (SD) model. L7Gn treatment improved depression-like and stress coping behaviors induced by SD stress, as confirmed by the tail suspension test and forced swimming test. Furthermore, L7Gn treatment reduced the blood corticosterone and hippocampal proinflammatory cytokine levels which were increased by SD stress, and L7Gn also increased the mRNA and protein levels of hippocampal brain-derived neurotrophic factor (BDNF) which were reduced by SD stress. Additionally, treatment with L7Gn resulted in increases in the phosphorylation of tropomyosin-related kinase B (TrkB), extracellular signal-regulated kinase (ERK), and cAMP response element-binding protein (CREB), which are downstream molecules of BDNF signaling. These findings suggest that L7Gn have therapeutic potential for SD-induced stress, via activating the BDNF signaling.
Keywords: Adaptation, Psychological; Animals; Antidepressive Agents; Brain-Derived Neurotrophic Factor; Depression; Disease Models, Animal; Hippocampus; Humans; Luteolin; Mice; Sleep Deprivation; Stress, Psychological; BDNF/TrkB/ERK/CREB signaling pathway; depression; luteolin-7-O-glucuronide; sleep deprivation; stress